Finite Element Evaluation of the Effect of Adhesive Creams on the Stress State of Dentures and Oral Mucosa - Anantha Narayanan Ramakrishnan; Oliver Röhrle; Christopher Ludtka; Roshan Varghese; Josephine Koehler; Andreas Kiesow; Stefan Schwan (Applied Bionics and Biomechanics)
The base fit between a removable partial denture (RPD) and the underlying soft tissue plays a significant role in its performance. The application of a denture adhesive is hypothesized to result in better retention of RPDs and, as a result, contribute to lower stress on the oral mucosa. The objectives of this study were to observe and compare the distribution of simulated bite forces applied to the RPD through the abutments and soft tissue for models with and without the use of a denture adhesive. Furthermore, we evaluated the possible benefit of using a denture adhesive in lowering stresses on the oral mucosa. The RPD, mandible, oral mucosa, abutment teeth supporting the RPD, and the corresponding abutment periodontal ligaments (PDLs) were modelled as 3D volumes based on computer tomography (CT) datasets. A viscoelastic adhesive layer between the RPD and oral mucosa was incorporated into this base model using Prony series approximation. The layer was developed as a volume extract using the denture surface. Finite element (FE) simulations were performed for the bite force on one of the RPD segments, with the resulting force and moments experienced by the dental structures and oral mucosa compared between the model with the adhesive layer and the base model without. As a result, the contact pressure on the oral mucosa for the model with the denture adhesive decreased to 0.15 MPa as compared to 0.25 MPa for the model without the adhesive. The potential role of denture adhesives in leading to a better fit between the RPD and oral mucosa as well as lowering contact pressures could be used to improve comfort in patients wearing RPDs.